Melanocytic or Not? Dermoscopy and Reflectance Confocal Microscopy for Lesions Difficult to Diagnose: A Cross-Sectional Diagnostic Accuracy Study - Camila Scharf (Mattioli1885, 2021)
Background: Different techniques for non-invasive skin examination and early diagnosis of skin lesions are available nowadays, being dermoscopy and reflectance confocal microscopy (RCM) the most diffused ones. Several studies supported the complementary use of dermoscopy and RCM that improves diagnostic accuracy when dealing with melanocytic lesions.